Mechanical properties and durability of fibre reinforced oil palm shell high strength lightweight concrete / Yew Ming Kun - Yew, Ming Kun (2015)
Oil palm shells (OPS) are agricultural solid end products produced by the oil palm manufacturing process. Palm trees grow in regions with hot climate and copious rainfall such as Malaysia, Indonesia and Nigeria. In Malaysia, oil palm fruits can be classified as dura, tenera, and pisifera. Different species and age categories of dura and tenera lightweight coarse aggregates are used in this study. The density of the shells is within the range of a majority lightweight aggregates and the specific gravity of the shells ranges between 1.15 and 1.37 g/cm3. A number of studies over the last two decades showed that the compressive strength of oil palm shell lightweight concrete is within 17-35 MPa and there is a reduction in density of 20-25% compared to normal weight concrete. Researchers have also found that oil palm shell lightweight concrete has lower mechanical and durability properties compared to normal weight and artificial lightweight aggregate concrete. Hence, a detailed investigation on the possibility of producing high strength lightweight concrete by using OPS and their effect on the mechanical and durability properties of the concrete are carried out in this study. In this study, it is found that high strength lightweight concrete with high workability can be produced by proper selection of OPS species and age categories of OPS. The results reveal that the use of 10 to 15-year-old crushed dura OPS (classified as ‘young prime’) gives a maximum achievable 28-day compressive strength of 54 MPa and dry density of about 1890 and 1996 kg/m3. The water absorption values for all high strength lightweight concrete investigated in this study are lower than 10%, which falls within the range of good concrete. It is also found that heat-treated OPS can be used to produce high strength lightweight concrete. The OPS are heat-treated at a temperature of 60 ⁰C over 0.5 h which gives a 28-day compressive strength of 49 MPa. In addition, the specimens can be categorized as good condition after three days based on the ultra pulse velocity test results. Another technique that can be used to compensate the low mechanical properties and durability of OPS concrete without increasing its density concrete is to reinforce the concrete with different types of polypropylene fibres. It is found that the addition of polypropylene fibres at an optimum volume fraction into OPS concrete significantly increases the compressive strength, splitting tensile strength and flexural strength compared with previous studies. In terms of durability and time-dependent performance, it is found out that the high strength lightweight concrete reinforced with heat-treated OPS and polypropylene twisted bundle fibres have low porosity, chloride ion penetration, water absorption, initial surface absorption and drying shrinkage values compared to OPS without heat treatment. Furthermore, the PPTB fibres can be used to reduce sensitivity of the oil palm shell concrete towards poor curing environments. The stress-strain curves of polypropylene fibre reinforced OPS concrete are indicative that the concrete is a ductile material. The findings of this study prove that PPTB fibres can be used as alternative materials to enhance mechanical the properties and durability of OPS lightweight concrete.